The management of business logistics - Coyle, John J.; Bardi, Edward J. (St. Paul ; New York : West Pub. Co., 1980)
This edition retains the basic thrust of the first edition to provide an introductory level text that emphasizes the nature of logistics functional relationship. The authors of this text have purposely oriented the material towards the introductory level, blending both the marketing and production impacts of logistics.
Includes bibliographical references and index
hza 27/07/2018
Loans
Keywords: Business logistics